Control Watering Nutrients for Rice Plants With a Drip Irrigation System Using Arduino and RTC - Haryanti, Tri; Fitriyanto, Indra; Maknunah, Jauharotul (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2024)
Indramayu Regency is one of the largest rice-producing areas in West Java, but its rice productivity, averaging 6 tonnes per hectare, falls short of the national target of 8 tonnes per hectare. One key problem contributing to this gap is the nutrient imbalance in rice plants, which can lead to pest and disease attacks. To address this, an automated drip irrigation system was developed to optimize nutrient delivery and improve crop yield. The aim of this study was to design a nutrient control system for hydroponic rice using Arduino and an RTC (Real-Time Clock), allowing for precise and scheduled watering of nutrients. The system contributes to better plant health, higher crop productivity, and more efficient use of water and nutrients. The method involved testing eight water pumps, each controlling different nutrient doses, in a hydroponic rice planting system. The system was set to irrigate according to a programmed schedule, with pumps activated at specific times to deliver nutrients to rice plants grown in polybags with fine sand. Data collection was conducted over 30 days by analyzing the condition of rice plant leaves for each nutrient dose. The results showed that the drip irrigation system successfully controlled nutrient delivery, and the analysis identified the optimal nutrient dose for healthy plant growth. In conclusion, the automated drip irrigation system using Arduino and RTC not only improved water and nutrient efficiency but also contributed to higher rice yield quality and quantity. The system shows promise for reducing production costs by lowering water and fertilizer usage while minimizing environmental impact.